Effect of platelet receptor gene polymorphisms on outcomes in ST-elevation myocardial infarction patients after percutaneous coronary intervention. (2nd January 2016) - Zhang, Jia-Hui; Wang, Jing; Tang, Xiao-Fang; Yao, Yi; Zhang, Yin; Ma, Yuan-Liang; Xu, Bo; Gao, Run-Lin; Song, Lei; Gao, Zhan; Chen, Jue; Wu, Yuan; et al.
Abstract: Polymorphisms in platelet receptor genes may influence platelet function. This study aimed to assess the impact of five polymorphisms of genes encoding platelet receptors on the risk of ischemic and bleeding events in ST-elevation myocardial infarction (STEMI) patients after percutaneous coronary intervention (PCI). 503 consecutive Chinese patients with STEMI after an uneventful PCI and exposed to standard dual antiplatelet therapy for 12 months were enrolled. Polymorphisms of platelet receptors, GPIa ( ITGA2, 807C > T, rs1126643), GPVI ( GP6, 13254T > C, rs1613662), PAR-1 ( F2R, IVS-14A > T, rs168753) and P2Y12 ( P2RY12, 34C > T, rs6785930 and H1/H2 haplotype, 52G > T, rs6809699) were detected by the ligase detection reaction. The follow-up period was 12 months. Overall, 34 (6.8%) ischemic events occurred and 46 (9.1%) major bleedings occurred. Multivariate Cox regression analysis showed the carriage of F2R rs168753 minor allele was an independent predictor of the composite ischemic events (HR 0.387, 95% CI 0.193–0.778, p = 0.008) after adjusted for established risk factors. Multivariate logistic regression model identified that carriage of P2RY12 rs6809699 minor allele (OR 2.71, 95% CI 1.298–5.659, p = 0.008) was an independent predictor of major bleedings. The associations were then validated in a second cohort of 483 STEMI patients. In STEMI patients after PCI, F2R rs168753 minor allele could significantly contribute to the risk of ischemic events, and P2RY12 rs6809699 minor allele could predict bleedings. The genetic testing of platelet receptors can be valuable in predicting adverse events in STEMI patients after PCI.